A water soluble β-glucan of an edible mushroom Termitomyces heimii: Structural and biological investigation. (10th December 2015) - Manna, Dilip K.; Nandi, Ashis K.; Pattanayak, Manabendra; Maity, Prasenjit; Tripathy, Satyajit; Mandal, Amit K.; Roy, Somenath; Tripathy, Sushri S.; Gupta, Nibha; Islam, Syed S.
Highlights: A branched β-glucan was isolated from the mushroom Termitomyces heimii. Structure of the glucan was established by chemical and 1D/2D NMR experiments. This polysaccharide showed biological activities. Abstract: A water soluble β-glucan (PS-I) with an average molecular weight ∼1.48 × 10 5  Da was isolated from the alkaline extract of an edible mushroom Termitomyces heimii . PS-I contained (1 → 3)-, (1 → 6)-, (1 → 3, 6)-linked and terminal β-d -glucopyranosyl moieties in a ratio of nearly 2:1:1:1. Based on the total hydrolysis, methylation analysis, periodate oxidation, Smith degradation, partial hydrolysis and 1D/2D NMR experiments the structure of the PS-I was elucidated. On the basis of these experiments, the repeating unit of the polysaccharide was found to consist of a backbone chain of two (1 → 6)-β-d -glucopyranosyl residues, one of which was branched at O -3 position with the side chain consisting of two (1 → 3)-β-d -glucopyranosyl and a terminal β-d -glucopyranosyl residue. Cytotoxic effect of PS-I on human blood lymphocytes at varied concentrations was studied. Moreover, it also exhibited potent antioxidant activities by diminishing the ROS and NO in the nicotine stimulated lymphocytes up to 200 μg/ml.